PENGARUH LITERASI E-FINANSIAL (KEMUDAHAN, KENYAMANAN, KEAMANAN) DAN KUALITAS LAYANAN PENGGUNA MOBILE BANKING TERHADAP KEPUASAN NASABAH (BRI UNIT KOTO BARU DHARMASRAYA TAHUN 2023) - Anisa, Rani; Gusteti, Yesi; Wiska, Mayroza (MANAJEMEN DEWANTARA, 2024)
The study aims to analyze the impact that e-finance literacy has on the ease, convenience, security and quality of mobile banking users’ services on customer satisfaction of the New Koto Unit. The era of globalization has been a major driver for the emergence of mobile banks’ rapid changes in technology and global connectivity has opened up new opportunities for the banking sector to provide more efficient and accessible services. The method of analysis of this research is to use a quantitative method with data collection using a questionnaire. The sample respondents in this study were taken from 282 customers using the new BRI mobile banking Koto Unit. Technical analysis tests validity, reliability, correlation, classical assumptions, double linear regression, and hypothesis testing. The results of the study showed that convenience had a partially positive and significant impact on customer satisfaction (t = 3,244 ), ( 0,001 < 0,05), while comfort had a positive and substantial influence on customer satisfying ( t = 4,872 ), ( 0,000 < 0,05), however, security had no significant effect on customer content ( t= 1,051 ), ( 0,291 > 0,05 ) while the quality of service had a significant and positive impact on client satisfaction.